Influences And Antecedents That Influence Home Purchase Decisions Through Sharia Mortgage Financing (Study On KCP BTN Syariah Kalimas Bekasi Branch Customers) - Siti Suparyanti; Christina Ekawati (Publikasi Indonesia, 2023)
This study aims to investigate the influence of marketing mix and service quality on customers' decision to purchase a house through Sharia financing at Bank BTN Syariah. The population of this research consists of customers who have purchased a house using Sharia financing from Bank BTN Syariah KCP Kalimas Bekasi. The sample size for this study is 150 individuals. The data analysis method employed in this research is multiple linear regression analysis. The results of the study show that both marketing mix and service quality have a significant simultaneous effect on customers' house purchase decisions. Furthermore, the partial results of the hypothesis test also indicate that marketing mix and service quality significantly influence customers' house purchase decisions. In conclusion, this research demonstrates that marketing and service quality factors play a crucial role in shaping customers' decisions to purchase a house through Sharia financing at Bank BTN Syariah KCP Kalimas Bekasi. Therefore, the bank needs to enhance service quality and marketing strategies to attract customers' interest in choosing Sharia financing as a solution for their house purchase